The background noise level of vertical pendulum tiltmeter in China - Ying Zhao (Geodesy and Geodynamics, 2020)
By using the observation data of the vertical pendulum tiltmeter in China, the influence of different sampling rates on the results of power spectral density is studied, and the background noise level of the seismic frequency band (200–600 s) of different stations and different types of instruments is emphatically analyzed. The conclusions are as follows: 1. The results of both single station and national statistics show that the noise levels of the two types of pendulum tiltmeter equal in the seismic frequency band; 2. There is no obvious regularity in the regional distribution, due to the influence of ocean and active tectonic movement, the noise levels of some stations in coastal areas are relatively high; 3. The curves of high noise level instrument are generally not smooth and burr-prone. Except for some stations affected by the ocean, they are mostly caused by the observation environment or the instrument itself. Keywords: Vertical pendulum tiltmeter, Power spectral density, Background noise